Prediction and Analysis of Spreading SARS CoV-2 Virus Using Machine Learning Techniques - Telugu Maddileti, Thokala Eswar Chand, Sankala Likhit Kumar, Danda Jahnavi Reddy (International Journal of Advanced Science and Technology, 2020)
COVID-19, the pandemic that has got the whole world worried, also called 2019-nCoV or 2019 novel coronavirus, is caused due to the virus called SARS CoV-2 which happens to be one of the kind of coronaviruses. The medical fraternity has not been able to find a cure to this dreadful disease till day. However, rigorous work is being carried out towards the same. During such times, it becomes difficult for the governments of various countries across the globe to maintain integrity and peace among the minds of the people. Therefore, for the government to take thoughtful decisions in the interest of the people of their country, they require a model or a way in which they can predict and analyse the way the disease is spreading across their territory. This paper puts forward a statistical machine learning model which uses the regularly updated data set consisting number of confirmed cases, active cases, recovered cases and deaths caused due to COVID-19 to predict and visualize the spread of the disease in different parts of the world. Thus, providing support to the decisions taken by the government officials.